2012
DOI: 10.1007/s12198-012-0102-y
|View full text |Cite
|
Sign up to set email alerts
|

Crew goal setting for security control

Abstract: This study investigated the effectiveness, efficiency, and robustness of simple goal setting in airport security control. As outcome, crew performance in terms of productivity (Experiment 1, field setting) was studied. Furthermore, the moderating role of negative and positive priming due to a previous task on the impact of goals (Experiment 2, laboratory setting) was analyzed. This research builds a bridge from goal setting theory to practice and prepares the grounds for its application in security or emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…This rise in detection also appeared in cases when simply introducing to the baggage scanner work team pre-intervention goals by supervisors. Others found ways to increase detection in overall team performance but it only lasted during short interventions (Wetter et al, 2013). A rare longitudinal study of screeners over a 4-year period with repeated measures found that screener competency in detecting prohibited items in x-ray images of passenger bags can be greatly improved through routine XRT training (Halbherr et al, 2013).…”
Section: Training and Performancementioning
confidence: 99%
“…This rise in detection also appeared in cases when simply introducing to the baggage scanner work team pre-intervention goals by supervisors. Others found ways to increase detection in overall team performance but it only lasted during short interventions (Wetter et al, 2013). A rare longitudinal study of screeners over a 4-year period with repeated measures found that screener competency in detecting prohibited items in x-ray images of passenger bags can be greatly improved through routine XRT training (Halbherr et al, 2013).…”
Section: Training and Performancementioning
confidence: 99%